Influência do treinamento físico combinado nas vias de sinalização da mTOR e da PGC-1α renal em ratos com diabetes experimental - Jorge, Luciana [UNIFESP] (2016)
Diabetes Mellitus (DM) is a multifactorial disease resulting from either failure in the secretion of insulin, and in the commitment of its action, leading to hyperglycemia and producing changes in the metabolism of carbohydrates, fats and proteins. These changes induce complications, among which stands out the diabetic nephropathy (DN). In these cases, the activation of molecular pathways plays an important role in the pathophysiological process. Studies indicated that regular physical exercise is an effective tool to decrease the progression of DN being indicated as a non-? pharmacological treatment. The aim of this study was to evaluate the benefits of aerobic and resistance exercise in the pathophysiology of ND with subsequent possibility of prescription of this type of training for both healthy subjects and diabetic, aimed to minimize the deterioration of renal function. In this study, Wistar rats were submitted to three different exercise training (ET) protocols, which were prescribed with intensity of 40 to 60%, based on the results of stress tests specific to each modality. Streptozotocin (STZ) was used to diabetes induction (50 mg / kg IV). Animals were separated into eight groups: four controls (non-?trained, trained resisted, trained aerobic and combined trained) and four diabetics (non-?trained, trained resisted, trained aerobic and combined trained), with 6 to 8 rats / group. Were analyzed blood glucose, response to the maximum test effort, weight and kidney function, renal histology and proteins expression in dynamic mitochondrial pathway (AMPK/Mfn2/DRP-?1) and renal hyperthrophy pathway (AKT/mTOR) (assessed by Western blot). Ours results showed that all ET modality can modulate the in dynamic mitochondrial pathway (p<0,05) and renal hyperthrophy pathway (p<0,05) when compared with the diabetics non trained, in addition the progression of diabetic nephropathy,atenued the proteinuria and renal dysfunction (p<0,05). This results showed that the associated the aerobic and resistance can be control/prevent the diabetic nephropathy, may be a non pharmacological treatments in a significant way.